Dual‐Functional Stacked Polymer Fibers for Stable Lithium Metal Batteries in Carbonate‐Based Electrolytes. Issue 10 (11th September 2022) - Han, Dong-Yeob; Song, Gyujin; Kim, Sungho; Park, Soojin
Abstract : Lithium (Li) metal has long been thought to be an ideal anode material for high‐energy‐density Li metal batteries (LMBs). Nonetheless, a variety of safety risks and short cycle life due to uncontrollable Li dendrite growth limit its practical application. Here, a novel polymer‐based 3D host composed of stacked polymer fibers (SPF) is purposefully designed using a simple electrospinning method to achieve dual‐functional properties that endow bottom‐up Li filling and morphologically regulate Li metal deposition over the host structure. As a result, the SPF allows for uniform Li‐ion flux in the electrode, leading to densely packed Li deposition and further stable cycling in conventional carbonate‐based electrolytes. Besides, a full cell paired with LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) cathode results in a high‐energy‐density battery with a low negative/positive capacity ratio and a wide operating temperature range. This study presents a rational design for improving the stability and safety of Li metal anodes in conventional carbonate‐based electrolytes for advanced LMBs. Abstract : Stacked polymer fibers with dual‐functional properties are fabricated using a simple electrospinning method, and they serve as an excellent 3D host. The incorporation of two different fibers suppresses lithium dendrites, allowing for uniformly deposited/dissolved Li metal up to 10 mAh cm −2 with densely packed morphology inside the host. The full cell improves cycle stability under a variety of operating conditions.